Laju perambatan retak fatik dan sifat mekanik pada pengelasan friction stir welding (FSW) aluminium AA2024-T3 dengan perlakuan transient thermal tensioning (TTT) - Pujono Pujono; Dian Prabowo; Ipung Kurniawan; Joko Setia Pribadi; Muhamad Yusuf (TURBO [Tulisan Riset Berbasis Online], 2022)
One type of engineering material that is often used in transportation construction, especially for aircraft, automotive, ships, and other industries is aluminum alloy. Aluminum alloys have excellent mechanical properties, including corrosion resistance, lightweight, and good formability. However, in addition to these good properties, aluminum also has a weakness, namely the appearance of porosity and cracks when connected using arc welding (TIG, MIG). Friction stir welding (FSW) is an appropriate welding method for aluminum alloys to overcome these weaknesses, but the next problem will arise, namely related to distortion, decreased mechanical properties, and residual stress. For this reason, additional treatment is needed in order to improve the mechanical properties of the FSW welding results. The research method to be carried out is to carry out the FSW welding process on 2024 T3 aluminum alloys by adding moving local heat or transient thermal tensioning (TTT) using a heater placed in front of the tool and a heating temperature of 200°C. Some of the characterizations that will be carried out are microstructure tests, tensile tests, and fatigue tests. The results showed that the highest tensile strength value was obtained in the 1500 specimen, which was 312.2 MPa. The microstructure in the nugget zone (NZ) is fine-grain equiaxed. The lowest fatigue crack propagation rate at ΔK values of less than 7 MPa.m0.5 occurred in the 1100 specimen, while in other specimens the fatigue crack propagation rate was higher.